1990
DOI: 10.1111/j.1476-5381.1990.tb14124.x
|View full text |Cite
|
Sign up to set email alerts
|

Pinacidil inhibits neuromuscular transmission indirectly in the guinea‐pig and rabbit mesenteric arteries

Abstract: 1 Effects of pinacidil were investigated on neuromuscular transmission in smooth muscle tissues of the rabbit and guinea-pig mesenteric arteries by both electrophysiological procedures and a bioassay of noradrenaline (NA) outflows. 2 Pinacidil (over 1 aM) hyperpolarized smooth muscle cell membranes in both tissues, in a concentration dependent manner. Pinacidil hyperpolarized and increased the ionic conductance of smooth muscle membrane more markedly in the rabbit mesenteric artery than in the guinea-pig. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

1991
1991
2007
2007

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 36 publications
1
7
1
Order By: Relevance
“…Glibenclamide is a selective inhibitor of this channel in vascular smooth muscles (Standen et al, 1989). In the present experiments, however, we observed that pinacidil (10pM) (Nakashima et al, 1990) and glibenclamide did not affect the inhibitory action of pinacidil. The extent of the contraction induced by high K+ is thought to be closely related to the [Ca21]i (Morgan & Morgan, 1984), yet 10,uM pinacidil inhibited the contraction without any decrease in [Ca2 +]; .…”
Section: Discussioncontrasting
confidence: 80%
“…Glibenclamide is a selective inhibitor of this channel in vascular smooth muscles (Standen et al, 1989). In the present experiments, however, we observed that pinacidil (10pM) (Nakashima et al, 1990) and glibenclamide did not affect the inhibitory action of pinacidil. The extent of the contraction induced by high K+ is thought to be closely related to the [Ca21]i (Morgan & Morgan, 1984), yet 10,uM pinacidil inhibited the contraction without any decrease in [Ca2 +]; .…”
Section: Discussioncontrasting
confidence: 80%
“…A similar, marginal permeability and a decrease of Cl − -permeability, pre-synaptic stimulatory effect was reported by Nederwhereas no change of Na + -permeability was obgaard 20 in rabbit pulmonary artery, by Nakashima served. 6 In line with these observations, it was shown and co-authors 21 in guinea-pig and rabbit mesenteric that pinacidil inhibits the NA-induced contraction of artery and by Fabiani & Story 15 in rat mesenteric rabbit mesenteric artery. 5 The two different Ca extent of inhibition of NA-induced contraction by This may explain the marginal stimulatory action of pinacidil ( Fig.…”
supporting
confidence: 53%
“…Indeed, it has been reported that in airway smooth muscle preparations [26], in the rat urinary bladder [27], in the rat vas deferens [28] and in the rabbit portal vein [11], pinacidil inhibits release of neurotransmitters. In contrast, in the guinea‐pig and rabbit mesenteric arteries, pinacidil and cromakalim had no effect on presynaptic neurotransmitter release [29,30]. However, these observations need further evaluation.…”
Section: Discussionmentioning
confidence: 99%